Advanced optical spectroscopy of new materials for luminescent solar concentrators - Carlos, Carlota Pereira de Almeida (2020)
The transition from the current energy matrix towards an environmentally friendly and a ordable energy sources is a crucial challenge of the 21st century. Fully energetically sustainable architecture is a strategic focus in this e ort, through the realisation of so-called net-zero energy buildings. This implies an increase in the use of renewable resources, such as the wind, tides and the sun. Hence, new technologies that integrate solar-harvesting devices into existing and newly constructed buildings are of growing relevance. Luminescent solar concentrators consist of a transparent matrix doped or coated with active optical centres that absorb the incident solar radiation, which is reemitted at a speci c wavelength and transferred by total internal re ection to the edges, where photovoltaic cells are located. This con guration enables photovoltaic devices to be embedded in building facades or windows, allowing them to be transformed into energy harvesting units. Challenges for the luminescent species in luminescent solar concentrators include the use of sustainable, natural-based organic molecules. In this scope, semitransparent amine-functionalized organic{inorganic hybrids (ureasils) incorporating two di erent natural-based organic dyes, chlorophyll and enhanced uorescent protein (eGFP), were synthesised and processed as thin lms and monoliths. The natural dyes' and organic-inorganic hybrid's excited state dynamics were studied and characterised { the absorption bands of chlorophyll a and eGFP were identi ed, as well as their characteristic emission in the red/NIR (600-750 nm) and visible (450-600 nm) spectral regions, respectively. The emission properties were further quanti ed through absolute emission quantum yield measurements, with the maximum values measured for the eGFP-doped di-ureasil hybrid (0:33 0:03) being two times higher than the maximum value found for the chlorophyll-doped hybrid samples (0:15 0:02). Fluorescent lifetime analysis was also performed resorting to two di erent techniques: time-correlated single photon counting and spectrally-resolved streak imaging, yielding uorescent emission lifetimes of 5 ns for chlorophyll and 2-3 ns for enhanced green uorescent protein, in solution and when incorporated into the hybrid hosts. Further analysis was carried out by tting a two exponential decay model to the uorescent decay curves of the for the green uorescent protein samples, considering that two distinct electronic states are responsible for the absorption around 488 nm and the emission at 510 nm. Based on the intriguing photoluminescent features of the dye-based samples, two prototypes of luminescent solar concentrators were fabricated and optically characterised. In particular, a liquid planar luminescent solar concentrator based on a glass container lled with eGFP dispersed in an aqueous solution and a eGFPdoped di-ureasil hybrid bulk planar luminescent solar concentrator. The devices were coupled to a silicon-based commercial PV device, revealing maximum optical conversion e ciencies of 2:99 0:01% (liquid) and 3:70 0:06% (bulk), illustrating the potential of this approach for the development of nature-based luminescent solar concentrators, meeting the requirements of reliable, sustainable and competitive energy systems.